Psychological Factors and Social Support in Adolescents with Suicidal Ideation: A Meta-Analysis - Zain Nadaa Nisriina; Epin Pakanna; Bhisma Murti; Aem Ismail (Journal of Health Promotion and Behavior, 2025)
Background: According to World Health Organization (WHO) data, as of August 28, 2023, there are more than 700,000 deaths due to suicide every year and the fourth highest cause of death in 18-29 years old is suicide. Studies report that psychological conditions and social support are risk factors for the emergence of suicidal ideation in adolescents. This study aimed to analyze and estimate the effect of psychological determinants (anxiety, loneliness, and depression), gender, and social support on suicidal ideation in adolescents. Subjects and Method: This was a meta-analysis with PICO model. Population: adolescents. Intervention: women, psychological determinants (anxiety, loneliness, and depression), and social support. Comparison: men, no anxiety, no loneliness, no depression, no social support. Outcome: suicidal ideation. The basic data used involves Google Scholar, PubMed, BMC, ScienceDirect, and Springer Link. The inclusion criteria are full-text articles with cross-sectional studies, published from 2018-2023, reported aOR. Data analysis using the Review Manager 5.3. Results: Meta-analysis was carried out on 16 primary studies from various countries, namely Ethiopia, Nepal, the United States, India, Slovenia, South Korea, Nigeria, Jamaica, China, the Netherlands, and Greece. Suicidal ideation decreased in male adolescents (aOR= 0.95; 95% CI= 0.73 to 1.24; p= 0.700) and strong social support (aOR= 0.84; 95% CI = 0.76 to 0.93; p <0.001). Loneliness (aOR= 2.86; 95% CI= 1.38 to 5.96; p= 0.005), anxiety (aOR= 2.46; 95% CI= 1.58 to 3.84; p<0.001), and depression (aOR= 5.46; 95% CI= 3.43 to 8.70; p<0.001) increased the risk of suicidal ideation. Conclusion: Suicidal ideation decreases in male adolescents and strong social support. It increases with loneliness, anxiety, and depression increase the risk of suicidal ideation.